(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: Current research aimed to compare the effects of fungal and bacterial phytase with or without citric acid (CA) on growth performance, serum mineral profile, bone quality, and nutrient retention in birds given non-phytate phosphorus (nPP)-deficient diets. Materials and Methods: A total of 216 Indian River broiler chicks were disturbed into six groups, namely, i) positive control (PC), ii) negative control (NC) contained 0.2% lower nPP than that in the PC diet, iii) NC + fungal phytase (Aspergillus niger), iv) NC + fungal phytase with 2% CA, v) NC + bacterial phytase (Escherichia coli), and vi) NC + bacterial phytase with 2% CA. Results: Compared to the PC group, the NC group showed poor performance, serum phosphorus (P) content, P retention, and bone quality. However, with the inclusion of phytase, all these phenomena were improved. The addition of bacterial phytase showed better values compared with fungal phytase. The main effects of phytase were significant for the feed conversion ratio (FCR), metabolizable energy conversion ratio (MECR), and P retention. The addition of CA, either with fungal or bacterial phytases, did not show considerable beneficial effects on overall performances. However, the main effects of CA were significant on the FCR, MECR, and crude protein conversion ratio. Conclusion: Incorporating bacterial and fungal phytase into low-nPP diets enhanced the broiler’s performance. The effects of bacterial phytase were more apparent than those of fungal phytase. However, the efficacy of phytase based on the source might relate to dose, and other factors need further investigation. Adv. Vet. Anim. Res., 11(2): 376-383, June 2024 http://doi.org/10.5455/javar.2024.k786